Effect of Kaolin as a Catalyst on the Yield of Catalytic Pyrolysis Of Waste Plastic Mixtures - Altohami, Eman Khaled; Mustafa, Mustafa Abbas (University of Khartoum Engineering Journal, 2022)
A waste plastic mixture of polypropylene (PP) and low density polyethylene (LDPE) was subjected to thermal degradation in the presence of kaolin as a catalyst. Different proportions of catalyst (5, 10, 15 and 20 wt. %) were added to the plastic wastes and mixed in a laboratory semi-batch reactor. The contents of the reactor were heated at a rate of 16℃/min, to reach the pyrolysis temperature of 400℃ at atmospheric pressure. The effect of feed and catalyst composition on the liquid product yield was determined. It is shown that the use of kaolin resulted in a decrease in the reaction time and an increase in the yield of the liquid fraction. The maximum liquid yield achieved, using plastic waste mixtures, is 90% for a mixture of PP: LDPE = 3:1 using 15 wt. % kaolin. The composition of the liquid product is analysed using a Gas chromatography–mass spectrometry (GC-MS). The liquid product is mainly composed of Hexadecanes and C16+ which is an indicator for heavy oil similar to diesel.